"It Changed Everything. And Not All in a Bad Way": Reflections of Pediatric Cancer Experiences. Issue 3 (3rd July 2017) - Molinaro, Monica L.; Fletcher, Paula C.
ABSTRACT: Pediatric cancer, otherwise known as childhood cancer, is devastating to both children and their families. All individuals in a family are often physically, psychologically, and socially affected. Using the qualitative theoretical orientation of interpretive phenomenology, interviews were conducted with 10 pediatric cancer survivors and 9 of their support persons to gain a more holistic understanding of the pediatric cancer experiences of children and their families. A total of 4 themes emerged from the data, however only the past experiences of the survivors and their recollection of their pediatric journeys will be discussed. Survivors experienced a variety of negative effects during and after treatment, while their support persons explained the emotional upheaval they experienced while caring for their children. Further, all individuals recalled positive memories throughout their journeys. The results of this study provide health care professionals and school administrators with insight into how to manage the difficult transitions children with cancer face when returning to school after cancer diagnosis and/or treatment. As well, this study may allow others undergoing similar journeys to relate to the lived experiences of the participants in this work.